Whither China? : Intellectual Politics in Contemporary China - Zhang, Xudong, 1965- (Book collections on Project MUSE., 2001)
Chinese cultural and intellectual politics waned after the Tiananmen Square incident. This volume explores their revitalization in the 1990s.